Kazakhstan and foreign experience in financing and encouraging eco-innovation projects - Karayilmazlar, E.; Suieubayeva, S.N.; Madiyarova , E.S. (BUKETOV BUSINESS REVIEW, 2017)
The article deals with the essence of eco-innovation projects and «green» technologies, studied the sources of financing of innovative projects in existing foreign and domestic practice. The main aspects of the activities of the International Development Bank in promoting sustainable «green» growth in member states of European Business Development Association are described. The purposes, tasks, the principles of support and stimulation of innovative projects, various institutes are revealed. Results of studying of the existing sources of financing of innovative projects on priority spheres of development of economy are systematized and conclusions are drawn on a possibility of practical application of these mechanisms.